Weight loss and changes in surface roughness of denture base and reline materials after simulated toothbrushing in vitro - Machado, Ana Lucia [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Vergani, Carlos Eduardo [UNESP]; Pavarina, Ana Claudia [UNESP]; Lopes Salles, Debora da Silva [UNESP]; Jorge, Janaina Habib [UNESP] (Wiley-Blackwell, 2012)
Objective: To evaluate the weight loss and the surface roughness of acrylic resins after simulated brushing tests.Material and methods: Ten specimens of each material (Tokuyama Rebase II-TR, New Truliner-NT, Ufi Gel Hard-UH and Lucitone 550-L) were made. The wear loss (mg) by weight and the surface roughness (Ra mu m) of each specimen was determined before and after brushing. The specimens were placed on the brushing machine and a total of 20 000 brushing cycles was performed. The results of weight loss and roughness values were submitted to the ANOVA followed by the Tukey's test (p = 0.05).Results: The mean weight loss of material L was statistically higher (p < 0.001) than that of the relines TR, UH and NT. No significant differences were found among the roughness values of resins TR, UH and L (p > 0.05). Only for L, toothbrushing increased the surface roughness. After toothbrushing, there was no significant difference between the roughness values of materials L and NT. The highest mean weight loss during the simulated toothbrushing tests was observed for L. Before the toothbrushing tests, the NT exhibited the highest mean roughness.Conclusion: Brushing resulted in increase in roughness only for resin L.
Keywords: weight loss; roughness; acrylic resin; toothbrushing